Evaluation of anti-diabetic activity of commercially available extracts of phyllanthus emblica in streptozocin induced diabetic rats - NISHANT PATHAK,; GYANENDRA KUMAR,; RAKESH CHANDRA CHAURASIA, (International Journal of Pharma and Bio Sciences, 2016)
Phyllanthus emblica (syn. Emblica officinalis) or amla, is supposed to rejuvenate all the organ systems of the body, provide strength and wellness. It keeps us away from all the diseases by boosting our immune system. Besides, Phyllanthus emblica plant is reported to possess many pharmacological and clinical properties.Objective: To evaluate the anti- diabetic activity of commercially available extracts Phyllanthus emblica on high fat diet and low dose streptozocin induced diabetic rats.Materials and Methods: Diabetes was induced in albino rats using streptozocin 35 mg/kg i.p after giving high fat diet for 2 weeks. Animals with fasting blood glucose (FBG) above 200 mg/dl one week after injecting streptozocin were randomly divided into four groups of six rats each. Group 1- Diabetic rats, received only the distilled water (control),Group 2 - Diabetic rats, received Phyllanthus emblica crude extract (200 mg/kg/day)– Phyllanthus emblica Low dose (PEL), Group 3– Diabetic rats, received Phyllanthus emblica crude extract (400 mg/kg/day) – Phyllanthus emblica High dose (PEH), Group 4– Diabetic rats, received Glibenclamide (0.6 mg/kg/day) - Standard (S). All the animals received the respective drugs for six weeks. FBG was measured every 2 weeks till the end of sixth weeks by glucose-oxidase method.Results: Commercially available extracts Phyllanthus emblica showed significant fall in fasting blood glucose (P<0.001) from second week onwards in comparison to diabetic control group.Conclusion: The results suggest that commercially available extracts Phyllanthus emblica have significant hypoglycemic activity in diabetic model.